Crystal Structure and Density Functional Theory Studies of Toxic Quinone Metabolites of Polychlorinated Biphenyls - Song, Yang (2011)
Lower chlorinated polychlorinated biphenyls (PCBs) are readily metabolized via hydroxylated metabolites to reactive PCB quinones. Although these PCB metabolites elicit biochemical changes by mechanisms involving cellular target molecules, such as the Aryl hydrocarbon receptor, and toxicity by interacting with enzymes like topoisomerases, only few PCB quinones have been synthesized and their conformational properties investigated. Similar to the parent compounds, knowledge of the three-dimensional structure of PCB quinones may therefore be important to assess their fate and risk. To address this gap in our knowledge, the gas phase molecular structure of a series of PCB quinones was predicted using HF/3-21G, B3LYP/6-31G** and UB3LYP/6-311G** calculations and compared to the respective solid state structure. All three methods overestimated the Cl-C bond length, but otherwise provided a reasonable approximation of the solid state bond angles and bond lengths. Overall, the UB3LYP/6-311G** level of theory yielded the best approximation of the molecular structure of PCB quinones in the solid state. Chlorine addition at the ortho position of both rings was found to increase the dihedral angle of the resulting quinone compound, which may have important implications for their interaction with cellular targets and, thus, their toxicity.